Bionomics of the Australian Hawk Moth, Theretra laterillii lucasii (Walker) (Lepidoptera: Sphingidae) - Kilaso, M.; Tigvattananont, S. (International Journal of Agricultural Technology, 2018)
Theretra latreillii lucasii (Walker) is an important insect pest of water primrose, Ludwigia hyssopifolia (G. Don). Eggs and larvae of T. l. lucasii were collected from L. hyssopifolia and raiseed in the entomological laboratory, King Mongkut’s Institute of Technology Ladkrabang. The number of laid eggs was 200-240 eggs per adult female. The egg incubation period lasted 3.47±0.15 days. After egg hatching, T. l. lucasii larvae go through five instars of developmental stages. Duration time of 1st to 5th instars was 3.79±0.50, 4.27±0.57, 3.26±0.50, 3.06±0.32 and 6.59±0.61 days, respectively. The body length was 4.73±1.16, 11.2±1.08, 16.33±1.35, 27.13±1.96 and 53.27±9.19 mm for 1st to 5th instar, respectively. The head capsule for 1st to 5th instar was 0.59±0.08, 0.91±0.06, 1.10±0.030, 2.28±0.15 and 3.87±0.18 mm wide, respectively. The length in mm for dorsal horn of 1st to 5th instar was 2.13±0.72, 3.67±0.62, 5.13±0.58, 5.57±0.46 and 5.63±0.64 mm long, respectively. Adults are medium in sizes with prominent heads and big eyes. The female lived longer than the male (8.40±0.92 and 6.47±0.91days, respectively). The principal host plants of T. l. lucasii are L. hyssopifolia and L. octovalvis in family Onagraceae. Moreover, Cayratia trifolia in family Vitaceae were found to be the food plant for T. l. lucasii.